The Association Between Serum Activin A Levels and Hypertension in the Elderly: A Cross-Sectional Analysis From I-Lan Longitudinal Aging Study. (22nd November 2017) - Tsai, Yi-Lin; Chang, Chun-Chin; Liu, Li-Kuo; Huang, Po-Hsun; Chen, Liang-Kung; Lin, Shing-Jong
Abstract: BACKGROUND: Hypertension is an important risk factor for cardiovascular disease. Activin A, a member of the transforming growth factor-β cytokine family, has been shown to regulate blood pressure through the renin–angiotensin system. However, the relationship between activin A and blood pressure remains uncertain. The objective of this study was to determine whether serum activin A levels are associated with blood pressure. METHOD: A total of 470 participants of I-Lan longitudinal Aging Study (ILAS) were eligible for this study. Serum levels of activin A were assessed by enzyme-linked immunosorbent assay. Cross-sectional analyses were performed, including comparisons of demographic characteristics, hypertensive status, and activin A levels. RESULTS: Among the study participants (50% men, mean age, 69 years), 236 (50.2%) were hypertensive and 234 (49.8%) were normotensive. Hypertensive patients had significantly higher serum activin A levels than normotensives (normotensive vs. hypertensive: 507 ± 169 vs. 554 ± 176 pg/ml, mean ± SD, P < 0.001). All subjects were divided into 3 tertiles on the basis of serum activin A levels. Increasing tertiles of activin A were associated with higher systolic blood pressure (SBP), diastolic blood pressure and pulse pressure (PP) (all P < 0.001). After adjusting for all the potential confounding factors, serum activin A concentration was still significantly associated with SBP ( P = 0.02) and PP ( P = 0.03). CONCLUSIONS: Serum activin A level was associated with SBP and PP. Further studies are required to assess their causal relationship and the clinical relevance.